CFD Investigation of Thermo-hydraulic Performance in Rib Roughened Fin Under Forced Convection - Srivastav, Ayushman (Journal of Graphic Era University, 2023)
Here, a for the purpose of investigating the thermo-hydraulic performance of, numerical simulation is performed. a fin with rib roughening and induced convection. The next paragraphs give the analysis. If we do numerical simulations under a variety of fluid flow situations and look at how they interact with one another, we might be able to obtain numerical information on the heat transfer and friction caused by a ribbed fin. We would need to examine how they interact in order to do this. There is a broad spectrum of rib pitch to rib height ratios (P/e) that are possible. it was feasible to gather data on fluid flow and temperature distribution in a validated numerical model by raising the Reynolds Number from 500 to 5000. These ratios were used to assess how effectively the model operated. To Charts that are based on the Nusselt Number and the friction factor are used in order to evaluate the thermal and hydraulic characteristics of rib-roughened fins. The findings from the rib roughened fin geometry are compared with those of a plain fin in order to determine the degree of efficiency that the test fin possesses in terms of eliminating heat from its base under operating conditions that are otherwise comparable to those previously described. This analysis was carried out to ascertain the degree of efficacy that the test fin possesses in terms of removing heat from its base. The ribbed fin’s P/e ratio of 6 contributes to the substantial increase in heat transport while also reducing friction.